2014
DOI: 10.1016/j.jcin.2013.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Initial Success Rate of Percutaneous Coronary Intervention for Chronic Total Occlusion in a Native Coronary Artery Is Decreased in Patients Who Underwent Previous Coronary Artery Bypass Graft Surgery

Abstract: The initial success rate of CTO-PCI of an NCA in the pCABG group was significantly decreased compared with that in the nCABG group. Anatomic complexity and unstable hemodynamic state were unfavorable conditions. This study reveals that the issues to be overcome are lying with CTO revascularization in an NCA in pCABG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 15 publications
3
50
0
Order By: Relevance
“…We also found that selected SVGs, either patent or occluded, can become very effective conduits for retrograde CTO PCI, and their use is associated with a very high final technical success and low complication. When we compared our single center CTO program data to those from Europe, Japan, and the USA [10][11][12]19,20 (Table 8), we found that our study population had one of the highest number of post-CABG CTO cases, comparable only to 1 American multicenter study of 2013 by Michael et al 20 We used a retrograde approach in post-CABG patients more frequently than anyone else. In the same post-CABG cohort, we performed retrograde CTO PCI via SVG more often than others.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We also found that selected SVGs, either patent or occluded, can become very effective conduits for retrograde CTO PCI, and their use is associated with a very high final technical success and low complication. When we compared our single center CTO program data to those from Europe, Japan, and the USA [10][11][12]19,20 (Table 8), we found that our study population had one of the highest number of post-CABG CTO cases, comparable only to 1 American multicenter study of 2013 by Michael et al 20 We used a retrograde approach in post-CABG patients more frequently than anyone else. In the same post-CABG cohort, we performed retrograde CTO PCI via SVG more often than others.…”
Section: Discussionmentioning
confidence: 76%
“…Histologically, native coronary CTO lesions of patients post-CABG are more extensively calcified 9 and therefore offer additional challenges that may also affect long-term outcomes. Only few studies have evaluated outcomes following CTO PCI in post-CABG patients, [10][11][12] and none reported longer-term outcomes.…”
mentioning
confidence: 99%
“…Prior CABG has been associated with higher procedural complexity and lower success rates, 20 although more recently we have demonstrated that similarly high success rates can be achieved among patients with and without prior CABG. 21 Achieving similarly high success rates among older lesions may in part be explained by use of the hybrid approach, which advocates early change of crossing strategy in case the initially selected approach does not provide prompt results.…”
Section: Discussionmentioning
confidence: 80%
“…If disease progression is not observed in the native coronary artery, then PCI for the native coronary vessel can be performed with equivalent risk and difficulty as observed preoperatively. On the contrary, if the proximal lesion in the native coronary artery progresses from ≤99 % stenosis to occlusion, then the difficulty and risk associated with PCI increase [3,4], and longer stents are usually required.…”
Section: Introductionmentioning
confidence: 99%